A new pygmy armadillo (Cingulata, Euphractinae) from the late Miocene of Andean Argentina reveals an unexpected evolutionary history of the singular Prozaedyus lineage. (June 2020) - Barasoain, Daniel; Contreras, Víctor H.; Tomassini, Rodrigo L.; Zurita, Alfredo E.
Abstract: The extinct euphractine Prozaedyus was recognized remarking the evident morphological resemblance of the dorsal carapace with the extant piche or pygmy armadillo Zaedyus pichiy . From a phylogenetic viewpoint, Prozaedyus has been interpreted as an early diverging Euphractinae restricted, at the moment, to the late Oligocene and early mid Miocene levels (Deseadan to Laventan SALMAs) of southern South America (Argentina, Chile, and Bolivia). We report here a specimen (MSJ-317) coming from the late Miocene (Loma de Las Tapias Formation; 9 Ma, Chasicoan Stage/Age) of western Argentina (San Juan Province), which represents a new species of Prozaedyus . The specimen includes an almost complete skull with complete dental series, some articulated fragments of the dorsal carapace and several isolated fixed and mobile osteoderms. Absence of teeth in the premaxillae, ornamentation pattern of fixed osteoderms, and presence of small foramina in the posterior and lateral margins of both mobile and fixed osteoderms, are characters that allow its inclusion within the genus Prozaedyus . Differences with the other known species of this genus include smaller size ( 35–40%), cranial characters (e.g. position of the infraorbital foramen, palatine suture, morphology of the occipital condyles), and ornamentation pattern of mobile osteoderms. The phylogenetic analysis carried out support its relation as a sister group of the other Prozaedyus species, revealing an ancient divergence for the new taxon, occurred before that of the late Oligocene-early mid Miocene forms, and a distant phylogenetic position from Zaedyus pichiy . This new finding represents the youngest record of the genus, extending its biochron several millions of years, and provides novel information on the poorly know post-Santacrucian forms. Additionally, the cranial anatomy of the new species suggests a carnivore/omnivore habit, similar to extant euphractine armadillos but contrary to the insectivore habit proposed for the other Prozaedyus species. Highlights: The biochron of the genus Prozaedyus extends to the late Miocene. Prozaedyus represents the most basal lineage among Euphractinae armadillos. Older known species of Prozaedyus represent more derived forms. New most modern species of Prozaedyus retain more plesiomorphic characters. First well characterized Prozaedyus species out of Patagonia area.